Identification and in vitro enzymatic activity analysis of the AOP2 gene family associated with glucosinolate biosynthesis in Tumorous stem mustard (Brassica juncea var. tumida) - Chen, Bing; Liu, Yu; Xiang, Chunfang; Zhang, Dandan; Liu, Zhuoyu; Liu, Yihua; Chen, Jingjing (Frontiers in Plant Science, 2023)
The major enzyme encoded by the glucosinolate biosynthetic gene AOP2 is involved in catalyzing the conversion of glucoiberin (GIB) into sinigrin (SIN) in Brassicaceae crops. The AOP2 proteins have previously been identified in several Brassicaceae species, but not in Tumorous stem mustard. As per this research, the five identified members of the AOP2 family from the whole genome of Brassica juncea named BjuAOP2.1-BjuAOP2.5 were found to be evenly distributed on five chromosomes. The subcellular localization results implied that BjuAOP2 proteins were mainly concentrated in the cytoplasm. Phylogenetic analysis of the AOP2 proteins from the sequenced Brassicaceae species in BRAD showed that BjuAOP2 genes were more closely linked to Brassica carinata and Brassica rapa than Arabidopsis. In comparison with other Brassicaceae plants, the BjuAOP2 members were conserved in terms of gene structures, protein sequences, and motifs. The light response and hormone response elements were included in the BjuAOP2 genes' cis-regulatory elements. The expression pattern of BjuAOP2 genes was influenced by the different stages of development and the type of tissue being examined. The BjuAOP2 proteins were used to perform the heterologous expression experiment. The results showed that all the five BjuAOP2 proteins can catalyze the conversion of GIB to SIN with different catalytic activity. These results provide the basis for further investigation of the functional study of BjuAOP2 in Tumorous stem mustard glucosinolate biosynthesis.